2009
DOI: 10.1158/1541-7786.mcr-09-0234
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Resected Human Brain Metastases of Breast Cancer Reveal the Association between Up-Regulation of Hexokinase 2 and Poor Prognosis

Abstract: Brain metastases of breast cancer seem to be increasing in incidence as systemic therapy improves. Metastatic disease in the brain is associated with high morbidity and mortality. We present the first gene expression analysis of laser-captured epithelial cells from resected human brain metastases of breast cancer compared with unlinked primary breast tumors. The tumors were matched for histology, tumor-node-metastasis stage, and hormone receptor status. Most differentially expressed genes were down-regulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 35 publications
5
144
0
1
Order By: Relevance
“…29 Although in normal brain and low-grade gliomas HK-I is the predominant isoform, HK-II is highly upregulated in human glioblastoma multiforme 30 and poor prognosis is associated with upregulation of HK-II in human brain metastases of breast cancer. 31 Thus HK-II upregulation is considered a consequence of metabolic re-programming in cancer.…”
Section: Hexokinase II In Metabolismmentioning
confidence: 99%
“…29 Although in normal brain and low-grade gliomas HK-I is the predominant isoform, HK-II is highly upregulated in human glioblastoma multiforme 30 and poor prognosis is associated with upregulation of HK-II in human brain metastases of breast cancer. 31 Thus HK-II upregulation is considered a consequence of metabolic re-programming in cancer.…”
Section: Hexokinase II In Metabolismmentioning
confidence: 99%
“…(36) In a clinical study, over-expression of HK2 was associated with brain metastasis of breast cancer. (37) The detailed molecular mechanisms that overexpression of HK2 causes in cancer cell invasion and metastasis are still unclear and it is a future research theme. Interestingly, we also found that GLUT1 was overexpressed in RCC cells and that GLUT1 was directly regulated by tumor-suppressive miR-1291.…”
Section: Discussionmentioning
confidence: 99%
“…Two homologues, Siah1 and Siah2, have been shown to be involved in the response to DNA damage, the hypoxic response, inflammation, and several oncogenic signals including those propagated by Ras and epidermal growth factor receptor (EGFR) [10][11][12][13]. To date, few studies have addressed the role of Siah expression in cancer, and there has been no consensus as to the biologic significance of such expression [14,15]. Thus, Siah expression and its role in the molecular pathogenesis of cancer, including NPC, remain unknown.…”
Section: Introductionmentioning
confidence: 99%